A systematic literature review of the sustainable transformational leadership practice and relevant impacts on school teachers’ organisational health / Dr. Daljeet Singh Sedhu ... [et al.] - Janah Singh, Daljeet Singh Sedhu; Baharun, Norhayati; Mohamad, Junainah; Hasbullah, Mohd Nasurudin (Universiti Teknologi MARA, Kedah, 2024)
The current study review aims to examine the sustainability of transformational leadership practice and organisational health in schools by thoroughly analysing the transformational leadership aspects and the conceptualisation of numerous fundamental leadership theories. Before conducting a systematic review, 34 articles were selected through a screening procedure by referring to the predefined criteria. Resultantly, a significant association between transformational leadership attributes and organisational health factors was revealed, which crucially functioned as the present study foundation. Specifically, four characteristics, namely ideal influence, inspirational motivation, intellectual stimulation, and self-interest, were significantly correlated with organisational health elements, including institutional commitment, peer leadership, faculty relationship, and academic focus.